A prospective randomised phase-II trial with gemcitabine versus gemcitabine plus sunitinib in advanced pancreatic cancer. Issue 1 (January 2015) - Bergmann, L.; Maute, L.; Heil, G.; Rüssel, J.; Weidmann, E.; Köberle, D.; Fuxius, S.; Weigang-Köhler, K.; Aulitzky, W.E.; Wörmann, B.; Hartung, G.; Moritz, B.; et al.
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most common malignant tumours and is still associated with a poor prognosis in advanced disease. To improve the standard therapy with gemcitabine, we initiated a prospective randomised phase-II trial with gemcitabine (GEM) versus gemcitabine plus sunitinib (SUNGEM) based on data of in vitro trials and phase-I data for the combination treatment. The rational of adding sunitinib was its putative antiangiogenic mechanism of action. Methods A total of 106 eligible patients with locally advanced, unresectable or metastatic PDAC without previous system therapy were randomised to receive GEM at a dosage of 1.000 mg/m2 d1, 8, 15 q28 versus a combination of SUNGEM at a dosage of GEM 1.000 mg/m2 d1 + 8 and sunitinib 50 mg p.o. d1–14, q21d. The primary end-point was progression free survival (PFS), secondary end-points were overall survival (OS), toxicity and overall response rate (ORR). Results The confirmatory analysis of PFS was based on the intend-to-treat (ITT) population (N = 106). The median PFS was 13.3 weeks (95% confidence interval (95%-CI): 10.4–18.1 weeks) for GEM and 11.6 weeks for SUNGEM (95%-CI: 7.0–18.0 weeks; p = 0.78 one-sided log-rank). The ORR was 6.1% (95%-CI: 0.7–20.2%) for GEM and for 7.1% (95%-CI: 0.9–23.5%) for SUNGEM (p = 0.87). The median time to progression (TTP) was 14.0 weeks (95%-CI: 12.4–22.3 weeks) for GEM and 18.0 weeks (95%-CI: 11.3–19.3 weeks) for SUNGEM (p = 0.60; two-sided log-rank). The median OS was 36.7 weeks (95%-CI: 20.6–49.0 weeks) for the GEM arm and 30.4 weeks (95%-CI: 18.1–37.6 weeks) for the SUNGEM (p = 0.78, one-sided log-rank). In regard to toxicities, suspected SAEs were reported in 53.7% in the GEM arm and 71.2% in the SUNGEM arm. Grade 3 and 4 neutropenia was statistically significantly higher in the SUNGEM arm with 48.1% versus 27.8% in the GEM arm (p = 0.045, two sided log-rank). Conclusions The combination SUNGEM was not sufficient superior in locally advanced or metastatic PDAC compared to GEM alone in regard to efficacy but was associated with more toxicity.